HOTS-BASED STUDENT WORKSHEET DEVELOPMENT TO IMPROVE STUDENTS’ VISUAL THINKING SKILLS IN SOLVING CALCULUS PROBLEMS - Asyhar, Beni; Sholihah, Ummu (MATEMATIKA DAN PEMBELAJARAN, 2024)
One alternative teaching subject that can support optimizing learning is student worksheets (SW). This development research with the ADDIE (Analysis, Design, Development, Implementation, and Evaluation) stages aims to describe the process of developing HOTS-based calculus subject SW to improve students’ visual thinking skills in solving valid, practical, and effective calculus problems. The subjects of this research were 2 classes of students from the Mathematics Education Study Program at UIN Sayyid Ali Rahmatullah Tulungagung fifth semester. Data was collected using questionnaires and problem-solving ability tests, and data analysis using MANOVA tests. The research results show that: 1) the HOTS-based SW developed is in the “valid” category so it can be used in calculus courses; 2) The practicality of HOTS-based SW can be seen from the results of student responses which are positive and in the “very good” category; and 3) The usability or effectiveness of HOTS-based SW is seen from the posttest results which show that there are differences in students’ visual thinking abilities in solving calculus problems between the experimental class and the control class. Keywords: HOTS; Problem Solving; SW; Visual Thinking